2022
DOI: 10.1038/s41593-022-01167-6
|View full text |Cite
|
Sign up to set email alerts
|

A tool for mapping microglial morphology, morphOMICs, reveals brain-region and sex-dependent phenotypes

Abstract: Environmental cues influence the highly dynamic morphology of microglia. Strategies to characterize these changes usually involve user-selected morphometric features, which preclude the identification of a spectrum of context-dependent morphological phenotypes. Here we develop MorphOMICs, a topological data analysis approach, which enables semiautomatic mapping of microglial morphology into an atlas of cue-dependent phenotypes and overcomes feature-selection biases and biological variability. We extract spatia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 78 publications
1
43
0
Order By: Relevance
“…Sex-specific differences exist in mouse microglial morphology, function, gene expression, and response to tauopathy, and the differences increase with age 63 66 . Our data identify a sex-dependent effect on therapeutic exposure and efficacy of CSF1R inhibition in Tg2541 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Sex-specific differences exist in mouse microglial morphology, function, gene expression, and response to tauopathy, and the differences increase with age 63 66 . Our data identify a sex-dependent effect on therapeutic exposure and efficacy of CSF1R inhibition in Tg2541 mice.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the observed reduction in phagocytic function, we observed that the loss of CYFIP1 expression in these iMGs results in increased ramification consistent with a less activated state. (67,73,74) Microglial motility into and within the CNS is also essential to proper neurodevelopment and maintenance functions. (75) These cells must first properly migrate from the primitive yolk sac to populate the developing brain during early development to become permanently brain-resident throughout life.…”
Section: Discussionmentioning
confidence: 99%
“…(72) Thus, various microglial morphotypes in these different contexts suggest a form-function relationship in which morphology and expression of various markers can be used as a proxy for functional state. (73, 74) CYFIP1 protein has been demonstrated to directly interact with the Wiskott-Aldrich syndrome protein member 1 (WAVE1) regulating dendritic cytoskeletal modulation of ARP2/3-mediated actin branching. (40-42) Our morphological characterization in CYFIP1 loss-of-function iPSC-derived microglia implicates a direct role in the cytoskeletal processes involved in proper function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex-specific differences exist in mouse microglial morphology, function, gene expression, and response to tauopathy, and the differences increase with age [63][64][65][66] . Our data identify a sexdependent effect on therapeutic exposure and efficacy of CSF1R inhibition in Tg2541 mice.…”
Section: Discussionmentioning
confidence: 99%